Conservation and diversification of the miR166 family in soybean and potential roles of newly identified miR166s. Issue 1 (December 2017) - Li, Xuyan; Xie, Xin; Li, Ji; Cui, Yuhai; Hou, Yanming; Zhai, Lulu; Wang, Xiao; Fu, Yanli; Liu, Ranran; Bian, Shaomin
Abstract Background microRNA166 (miR166) is a highly conserved family of miRNAs implicated in a wide range of cellular and physiological processes in plants. miR166 family generally comprises multiple miR166 members in plants, which might exhibit functional redundancy and specificity. The soybean miR166 family consists of 21 members according to the miRBase database. However, the evolutionary conservation and functional diversification of miR166 family members in soybean remain poorly understood. Results We identified five novel miR166s in soybean by data mining approach, thus enlarging the size of miR166 family from 21 to 26 members. Phylogenetic analyses of the 26 miR166s and their precursors indicated that soybean miR166 family exhibited both evolutionary conservation and diversification, and ten pairs of miR166 precursors with high sequence identity were individually grouped into a discrete clade in the phylogenetic tree. The analysis of genomic organization and evolution ofMIR166 gene family revealed that eight segmental duplications and four tandem duplications might occur during evolution of the miR166 family in soybean. The cis-elements in promoters ofMIR166 family genes and their putative targets pointed to their possible contributions to the functional conservation and diversification. The targets of soybean miR166s were predicted, and the cleavage ofATHB14-LIKE transcript was experimentally validated by RACE PCR. Further, the expression patterns of the five newly identifiedMIR166 s and 12 target genes were examined during seed development and in response to abiotic stresses, which provided important clues for dissecting their functions and isoform specificity. Conclusion This study enlarged the size of soybean miR166 family from 21 to 26 members, and the 26 soybean miR166s exhibited evolutionary conservation and diversification. These findings have laid a foundation for elucidating functional conservation and diversification of miR166 family members, especially during seed development or under abiotic stresses.